The Postglacial Rebound Signal of Fennoscandia Observed by Absolute Gravimetry, GPS, and Tide Gauges - Bjørn Ragnvald Pettersen (International Journal of Geophysics, 2011)
We have compiled time derivatives of gravity and vertical motion for a dozen sites in Fennoscandia. Time series of absolute gravimetry and permanent GPS cover a time span of about a decade. Tide gauges have operated for many decades near seven of the sites. Linear relations are found to range from −0.17 to −0.22 for the slope between gravity and vertical uplift rates. An eustatic sea level rate of 1.2 mm/year is derived from these data. This compares well with results for North America and with theoretical predictions for viscoelastic Earth models.